ANALISIS KINERJA APARATUR PEMERINTAH DALAM MEMBERIKAN PELAYANAN PUBLIK PADA BADAN PENANGGULANGAN BENCANA DAERAH KOTA PAYAKUMBUH - Yamsasni, Yamsasni; Putera, Roni Ekha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research is motivated by the fact that the performance of BPBD apparatus in providing public services will be largely determined by various interrelated factors, especially the availability of adequate apparatus resources in quantity and quality, as well as the availability of supporting facilities and infrastructure. This research uses a qualitative method using an analytical approach with a purposive sampling technique and is then analyzed using data reduction, data display, and drawing conclusions. The research results show that the performance of government officials in providing public services to the Payakumbuh City Regional Disaster Management Agency can be seen in the City BPBD Facilities and Infrastructure, human resources, and the Payakumbuh City BPBD Strategy. Then to improve the performance of the apparatus by increasing the ability of the apparatus to complete the work, completing the facilities and infrastructure, and following the strategy carried out by BPBD Payakumbuh City in improving the performance of the apparatus, namely completing the lack of facilities and infrastructure, Lastly, public policy regarding the performance of the Payakumbuh City BPBD in providing services can be seen in Regional Regulation Number 13 of 2013 concerning the Payakumbuh City BPBD and Payakumbuh Mayor Regulation Number 32 of 2013 concerning the main tasks and functions of the Payakumbuh City Regional BPBD, as well as Ministerial Regulation for the Empowerment of State Apparatus Number PER/09/M.PAN/4/2007 concerning general guidelines for main performance within government agencies, including BPBD Payakumbuh City.